Governance Development Marketplace in Cameroon : Lessons Learned - World Bank (Washington, DC, 2015)
Governance is a major challenge to Cameroons development. Weak governance affects most economic transactions and hampers delivery and quality of services. Based on Cameroon’s development strategy (as expressed in the 2035 vision and the 2009 growth and employment strategy), the objective of the World Bank 2010-2014 Country Assistance Strategy (CAS) is to boost inclusive growth, through increased competitiveness and improved service delivery. Governance is a cross-cutting theme in the CAS and for World Bank operations. To support the governance agenda in Cameroon, the World Bank has mobilized funds through the multi-donor Governance Partnership Facility (GPF) for the Banking on Change Governance Program in Cameroon (hereafter the ‘Governance Program’), which became active in March 2010. The objective of the GPF-funded Governance Program is to increase transparency, accountability, and participation related to key governance issues in selected sectors in Cameroon. This report describes output, lessons, and conclusions from the GDM component. GDM’s main output, the Development Marketplace (DM), is described in detail and results and lessons learned are described for both the DM and the GDM as a whole. Other activities under the GDM include a large knowledge sharing event, support to a South-South exchange and seven DM finale debates. Sources for the report include written material (e.g. Catholic Relief Services’ (CRS) evaluation report of GDM, summaries of financed activities, feature stories, GDM Finale event guide) and interviews with GDM participants and World Bank staff.